Behavior of canola hybrids and their F2 generations: physiological and sanitary seed quality (Revista de Ciências Agroveterinárias, 2017)
The objective of this study was to compare the physiological and sanitary quality of canola hybrids and their respective F2 generations. The F2 generation seeds of commercial canola hybrids Hyola 61 and Hyola 433, harvested in July 2014, were evaluated as well as the hybrid seeds. The factorial arrangement (2x2) (Hybrid x Generation) in a completely randomized design was used, with four replications. The germination tests were carried out, tetrazolium, electrical conductivity and seed health, based on the percentage of contaminated seeds. The obtained seedlings had both shoot and root system length measured. The sanitary quality was assessed based on the percentage of seeds contaminated with Aspergillus spp. and Colletotrichum spp. fungi. There was a significant interaction between F2 generations and hybrids for the first count characteristics (PCG), second germination count (SCG) and shoot length (CPA). On the physiological quality, reduction in germination occurred only for hybrid Hyola 61, having approximately 43% less than the hybrid seeds germinated for the F2 generation. There were also differences between generations of abnormal seedlings characteristics and electrical conductivity, and the F1 progeny showed higher values for both. With regards to health quality, Aspergillus spp. and Colletotrichum spp. fungi. were checked, but there was no difference in the the F1 and F2 seeds and neither for hybrids. In the present study, there was differential behavior to the variable seed germination between the F1 and F2 generations; unlike the health quality was not reduced, showing no difference between hybrids and generations.
Keywords: Brassica napus L. var. Oleifera Moench; Oil crops; Saved seeds; Hybrid seed.